Early childhood teachers’ writing beliefs and practices - Bingham, Gary E.; Gerde, Hope K. (Frontiers in Psychology, 2023)
This study examined the early writing beliefs, ideas, and practices of 54 early childhood teachers. Teachers completed a survey designed to examine their early writing beliefs and provided definitions about early writing development through a written response. Teachers were also observed in their classrooms and writing practices were coded for instructional strategy employed by the teacher (i.e., modeling and scaffolding approaches) and the instructional focus of these interactions with attention to early writing skill. Teachers’ definitions of writing often emphasized specific writing skills, with most teachers emphasizing handwriting. Teachers were observed enacting a range of modeling and scaffolding practices to support early writing, but the majority of interactions focused on handwriting supports. Teachers’ definitions of writing and their responses to the teacher belief survey were unrelated to each other, but differentially related to writing skills emphasized in interactions with children. Teachers who identified more than one writing component in their definition were more likely to enact practices to support children’s writing concept knowledge, while teachers who espoused more developmentally appropriate early writing beliefs on the survey were more likely to engage children in spelling focused interactions. Findings have implications for the study of teachers’ beliefs about writing as well as the need for professional learning supports for preschool teachers.